Durability of SARS-CoV-2 IgG response: a cross-sectional study in vaccinated healthcare workers using dried blood spot and multi-antigen profiling - Imam Nurjaya; Erwin Arief; Nur Ahmad Tabri; Irawaty Djaharuddin; Bulkis Natsir; Sitti Nurisyah; Joko Hendarto; Ansariadi Ansariadi; Rasiha Rasiha; Moh. Anfasa Giffari Makkaraka (Exploration of Immunology)
Aim: Assessing severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) immunoglobulin G (IgG) antibodies among healthcare workers (HCWs) is crucial in understanding the durability of humoral immune response due to vaccination and the post-pandemic era. Therefore, this study aimed to evaluate IgG antibody seroprevalence, IgG levels, and long-term durability responses after the coronavirus disease 2019 (COVID-19) pandemic in HCWs. Methods: The cross-sectional study recruited HCWs aged ≥ 18 years, vaccinated at least once, and without autoimmune diseases at Dr. Wahidin Sudirohusodo Hospital Makassar. Antibody titers against spike protein, nucleocapsid protein, and spike-nucleocapsid conjugate were quantified using dried blood spot (DBS) samples and multi-antigen profiling (xMAP) technology to measure seroprevalence. Results: The results showed that there was a total of 103 participants with the majority being female (59.22%), ≤ 40-year-old (87.38%), nurses (56.31%), had no comorbidities (88.35%), and were infected with COVID-19 (70.87%). A significant proportion received three times vaccination (76.7%), while 102 of 103 (99.03%) showed seropositivity. IgG showed the highest mean antibody titers for spike protein [10,819.38 ± 2,554.23 mean fluorescence intensity (MFI)] in the first 6–12 months after the last vaccinations. Meanwhile, the IgG titer (MFI) showed a long duration over 30 months. Vaccine significantly influenced spike protein antibody levels, with the highest observed in the group receiving a combination of two inactivated vaccines followed by two messenger ribonucleic acid (mRNA) vaccines (p < 0.05). Conclusions: HCWs showed a sustained humoral immune response to SARS-CoV-2 for over 24 months post-vaccination. The type and combination of vaccines administered were significantly correlated with the IgG antibody levels, suggesting the long-term efficacy of the vaccination regimens. The application of DBS and xMAP technology in the study facilitated the assessment of SARS-CoV-2 IgG responses, offering valuable insights into the dynamics of immune persistence following vaccination.